PENGELOLAAN PEMBELAJARAN FIQIH DENGAN PENDEKATAN KONTEKSTUAL PADA MADRASAH ALIYAH SWASTA JATUH (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
The development of strategies and approaches in the fiqh learning process in madrasas aliyah through a contextual approach is expected to create an active learning process that fosters student enthusiasm and interest in learning. The purpose of this study was to determine the planning, management and evaluation of the implementation of fiqh learning by Islamic Religious Education Teacher by using a contextual approach in Madrasah Aliyah Swasta Jatuh. Descriptive method with a qualitative approach is used through observation and interview techniques to fiqh teachers. The results showed that learning planning has been carried out with good preparation, including by formulating a complete component: objectives, materials, strategies, methods, techniques, tactics, syllabus development and learning preparation; The management of learning has been carried out in accordance with the implementation of contextual approaches, namely through the stages of constructivism; Inquiry, Questioning, Learning Community, Modeling, Reflection, and Authentic Assessment; The evaluation of learning uses classroom-based assessment. This is in accordance with the demands of implementing the curriculum 2013.